THE USE OF AUSTRALASIAN DEBATE SYSTEM TO IMPROVE SPEAKING ABILITY OF ENGLISH CONVERSATION CLUB (ECC) MEMBERS’ OF SMA N 1 KUDUS - Kurniati, Diah; Romadlon, Farid Noor (SIMPLE: International Journal of English Education, 2025)
Being able to speak English is important nowadays. It is a global language which is used in every part of life. As a foreign language, English has different position in Indonesian learners or students rather than those who are in English–second language countries. More students still regard English as subject should be accepted only in the class. This is one of factors students are difficult to master English, especially in speaking. Speaking English becomes something which is difficult since it is not practiced. A language must be used, must be applied as the medium of communication. Regarding to the purpose of communication, speaking relies on the message conveyed and the way it is delivered. Speaking basically is easier than other skills in English (Listening, Reading, and Writing). Unfortunately, most students feel have less confidence for speaking English. They are afraid for making mistakes. Knowing this condition, it is needed an intensive treatment through certain techniques so students will get used to talk in English without any barrier. Besides, their mental should be also sharpened so they will not be afraid to speak in English to others, moreover to public or in front of public. Therefore, researchers are eager to expose students’ speaking ability in the English Conversation Club (ECC) of SMA N 1 Kudus by using an Australasian Debate System. This technique will give more opportunity for students to explore their idea individually and in a team.